Technological impediments to business-to-consumer (B2C) electronic commerce - Ab Aziz, Azlina (2005)
The information age is rapidly changing the world in which we live. Given the increasing dominance of the Internet and the World Wide Web (WWW), many functions in our society are rapidly becoming transacted via computer. Internet and World Wide Web technologies provide the infrastructure for the Electronic Commerce (e-Commerce) revolution now taking place. As a result of these technologies, even the smallest organization can afford to market its wares to hundreds of millions of potential e-Consumers. However, these technologies also pose threats to the very electronic commerce which they enable. For managers to strategize and implement e-Commerce effectively in their organizations, these impediments need to be recognized and understood. The goal of this paper is to identify the primary technological impediments to e-Commerce. Six categories of technological impediments have been identified. Those which appear to pose the greatest threats to the development of e-Commerce are: (1) download delays, (2) limitations in the interface, (3) search problems, (4) inadequate measurement of Web application success, (5) security (real and perceived) weaknesses, and (6) a lack of Internet standards. Associated costs, threats, and limitations specific to e-Commerce are also identified and implications explored. The paper concludes with an assessment of ways to mitigate these obstacles, including design choices, workarounds, and emerging technological solutions.